Integrating mind-body processes and motivational interviewing in health coaching: enhancing support for health behavior change - Wolever, Ruth Q.; Weinand, Rebecca (Frontiers in Psychology, 2025)
The global rise of chronic disease presents a need for effective prevention and treatment grounded in mind–body science and autonomy-promoting lifestyle interventions. Health and wellness coaching (HWC) has emerged as a new field as the evidence for it has grown. However, there continue to be significant discrepancies in how the HWC role is defined, trained, and practiced. HWC is an evidence-based approach integrating well-established behavior change theories and techniques to help individuals explore and sustain self-determined health targets. The National Board for Health and Wellness Coaching in the United States guides credentialling for the field and establishes minimum training standards and competencies for practicing health coaches. Foundational knowledge of the mind–body connection is newly included in these coach competencies. In this paper, we present the overall process of HWC used in the Vanderbilt Health Coaching Program, emphasizing how mind–body processes can be integrated with motivational interviewing. We specifically present three mind–body processes that we have entwined with motivational interviewing and iterated with over 700 trainees: use of mindfulness, the whole person Wheel of Health, and guided visualization. We also present two structural tools that overlay the mind–body processes and motivational interviewing: the Vanderbilt Health Coaching Funnel and it’s brief derivative for clinical encounters, the IVA (Importance Visioning Activation) Funnel. Each mind–body process and the two structural tools are described in detail as each promotes the underlying development of sustainable behavior change. Our aim is that these mind–body processes and structural tools will help clarify the evidence-based strategies upon which true coaching is developed and that other clinicians, researchers, and coaches will utilize them to empower their patients in pursuing their best health.